Growth and yield Responses of Capsicum (Capsicum annuum) Intercropped with Maize(Zea mays) - Kanatharan, Y.; Sivachandiran, S.; Sivakumar, S. (Vavuniya Campus Annual Research Session-2009, 2009)
Effect of planting pattern of capsicum in maize in an intercropping system was studied at the District Agricultural Training Centre (DATC), Thirunelvely, during the period from November 2008 to March 2009. The experiment was carried out with four treatments in Randomized complete block design (RCBD) with three replicates. The same population of maize comprised (120cm × 30cm) spaced single rows (T1 and T2) and (60cm × 45cm) spaced double rows (T3 and T4) as a main crop was maintained treatments, while capsicum were planted at a recommended spacing of 30cm × 15cm but inter row spacing of maize and capsicum plant population varied with treatments. Capsicum was planted 20 days after planting of maize. Growth and yield parameters of maize and capsicum were recorded and analysed. The experiment results were tested significance at α=0.05. Plant height and yield of the maize did not differ significantly among treatments. Plant height of capsicum among treatments was significantly differed. Fruit length was not significantly different among the treatments. Yield was significantly higher in T2 than other treatments. Light intensity was also significantly differed in all treatments. However the interception of light was higher in treatments with two rows of maize (T3 and T4). Land equivalent ratio (LER) was significant among treatments and highest was recorded in T2 (1.59). Net income was also higher in the treatment T2. Considering yield, profit and other quality parameters, three rows of capsicum with single rows of maize (T2) can be recommended as a better spacing option for intercropping capsicum with maize at Maha in calcic red yellow latasol soil.
Keywords: Intercropping System; Inter and Intra row Spacing; Plant Population; Maize; Capsicum; Land Equivalent Ratio